2014
DOI: 10.1007/s11357-014-9650-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute bouts of endurance exercise on retinal vessel diameters are age and intensity dependent

Abstract: Alterations of retinal vessel diameters are associated with increased cardiovascular risk. We aimed to investigate changes in retinal vessel diameters in response to acute dynamic exercise of different intensities and whether these changes are age dependent. Seventeen healthy seniors (median (IQR) age 68 (65, 69) years) and 15 healthy young adults (median (IQR) age 26 (25, 28) years) first performed a maximal treadmill test (MTT) followed by a submaximal treadmill test (SMTT) and a resting control condition in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 38 publications
6
18
1
Order By: Relevance
“…In such patients, intensive exercise and the increase in blood pressure may lead to retinal damage due to even further impaired autoregulation. On the other hand, further studies are needed to assess whether physical activity and potential hemodynamic adaptations could lead to improved vascular reactivity [17]. The finding regarding the potential benefit of frequent physical activity is also in line with the current ADA recommendations for physical activity in individuals with type 1 diabetes [15].…”
Section: Discussionsupporting
confidence: 68%
“…In such patients, intensive exercise and the increase in blood pressure may lead to retinal damage due to even further impaired autoregulation. On the other hand, further studies are needed to assess whether physical activity and potential hemodynamic adaptations could lead to improved vascular reactivity [17]. The finding regarding the potential benefit of frequent physical activity is also in line with the current ADA recommendations for physical activity in individuals with type 1 diabetes [15].…”
Section: Discussionsupporting
confidence: 68%
“…Age has been suggested to influence the physiological responses to exercise. Several studies have reported age-related differences in exercise responses [25][26][27][28]. Supporting these human studies, animal models also indicate that age-related responses to exercise can be seen in cognition [29,30], in BDNF [30], and in microvascular function [31].…”
Section: Accepted Manuscript 1 Introductionmentioning
confidence: 77%
“…The retinal vessels offer a unique and easily accessible window through which to study human microcirculation in health and disease. As an important physiological parameter, the retinal vessel diameter has been found to alter in various diseases [ 24 27 ], as well as to change with age and exercise intensities [ 28 , 29 ]. Researchers have proposed retinal vessel diameter as a biomarker with which to determine the risk and progress of cardiovascular disease [ 30 33 ].…”
Section: Discussionmentioning
confidence: 99%